2019
DOI: 10.1002/cssc.201900365
|View full text |Cite
|
Sign up to set email alerts
|

Selective Transformations of Triglycerides into Fatty Amines, Amides, and Nitriles by using Heterogeneous Catalysis

Abstract: ZrO 2 -supported Pt clusters;i i) the amidation of triglycerides under gaseous NH 3 catalyzed by high-silica H-beta (Hb)z eolite at 180 8C; iii)the Hb-promoted synthesis of nitrilesf rom triglycerides and gaseous NH 3 at 220 8C. These methods are widely applicable to the transformation of various triglycerides (C 4 -C 18 skeletons)i nto the corresponding amines,a mides, and nitriles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 74 publications
1
28
0
1
Order By: Relevance
“…5b, L2) as privileged ligands in combination with a ruthenium or cobalt precursor. Notable developments from 2015 to 2019 reached in the field of heterogeneous catalysis were described by the groups of Kim 146 148 respectively, were showcased as active systems.…”
Section: Related Catalytic Hydrogenative Transformationsmentioning
confidence: 99%
“…5b, L2) as privileged ligands in combination with a ruthenium or cobalt precursor. Notable developments from 2015 to 2019 reached in the field of heterogeneous catalysis were described by the groups of Kim 146 148 respectively, were showcased as active systems.…”
Section: Related Catalytic Hydrogenative Transformationsmentioning
confidence: 99%
“…[66][67][68][69][70][71][72] Among biomass materials, triglycerides serve as the most important feedstocks for the synthesis of fatty amines, amides, nitriles and alcohols used in the production of surfactants, polymers and other useful commodity chemicals. 73 However, benign manufacturing processes for the direct transformation of triglycerides into these chemicals are not well developed. In this study, we demonstrated the potential applicability of Re(5)/TiO2 catalyzed hydrogenations to direct transformation of triglycerides into the corresponding alcohols.…”
Section: Selective Hydrogenation Of Triglyceridesmentioning
confidence: 99%
“…Oils undergo the biocatalysis process using ethanolamide, as evidenced in the Mass spectrometry (MS) profile when samples showed characteristic signals ofFAAs, as observed in other characterization studies of these compounds using Fourier transform infrared analysis (FTIR), and in previous studies that have used the Gas chromatography mass spectrometry (GC-MS) technique to quantify fatty acid and fatty acid amide content in various sample types [47,51]. Other studies also have obtained fatty amides from direct amidation of triglycerides from other natural sources [38,52].…”
Section: Discussionmentioning
confidence: 73%
“…The most frequent biosynthetic routes for these endocannabinoids are through arachidonic acid and involve compounds that are easily obtained (by chemical synthesis) and can be developed in the presence of a metallic catalyst [32,33] or biocatalyst [34,35]. Another possibility is based on the direct reaction from rich fatty acid oils from plants with amine that appear to be feasible for a biosynthetic route [36][37][38].…”
Section: Introductionmentioning
confidence: 99%